EXPANDING THE ROLE OF EDUCATION IN EATING DISORDER PREVENTION: THE ROLE OF A SOCIO-CULTURAL APPROACH - Laužonytė, Alma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The research on eating disorder (ED) prevention, evolving since the mid-1990s has primarily focused on medical and psychiatric perspectives, emphasising diagnosis and treatment. At the same, there is a growing recognition that prevention efforts, despite their critical importance, are underrepresented in academic literature. This study aims to promote a more holistic approach, integrating education as a pivotal socio-cultural factor in ED prevention. The study delineates a shift from a predominantly medical model to a more inclusive socio-cultural framework. It stresses the need for interdisciplinary collaboration and emphasises the critical role of educational strategies in the broader context of ED prevention. The aim of this article is to conduct a review of the scientific literature in order to provide a clearer picture of general research trends and paradigms in ED, and to expand the role and relevance of ED prevention in an educational context. While acknowledging that social environments including micro, meso, macro systems influence the development of ED, this paper focuses on the meso environment, highlighting the importance of schools and school professionals in preventing ED.